Synthesis and Evaluation of Poly(3-hydroxypropyl Ethylene-imine) and Its Blends with Chitosan Forming Novel Elastic Films for Delivery of Haloperidol - Sitthiphong Soradech; Pattarawadee Kengkwasingh; Adrian C. Williams; Vitaliy V. Khutoryanskiy (Pharmaceutics, 2022)
This study aimed to develop novel elastic films based on chitosan and poly(3-hydroxypropyl ethyleneimine) or P3HPEI for the rapid delivery of haloperidol. P3HPEI was synthesized using a nucleophilic substitution reaction of linear polyethyleneimine (L-PEI) with 3-bromo-1-propanol. 1H-NMR and FTIR spectroscopies confirmed the successful conversion of L-PEI to P3HPEI, and the physicochemical properties and cytotoxicity of P3HPEI were investigated. P3HPEI had good solubility in water and was significantly less toxic than the parent L-PEI. It had a low glass transition temperature (Tg = −38.6 °C). Consequently, this new polymer was blended with chitosan to improve mechanical properties, and these materials were used for the rapid delivery of haloperidol. Films were prepared by casting from aqueous solutions and then evaporating the solvent. The miscibility of polymers, mechanical properties of blend films, and drug release profiles from these formulations were investigated. The blends of chitosan and P3HPEI were miscible in the solid state and the inclusion of P3HPEI improved the mechanical properties of the films, producing more elastic materials. A 35:65 (%w/w) blend of chitosan–P3HPEI provided the optimum glass transition temperature for transmucosal drug delivery and so was selected for further investigation with haloperidol, which was chosen as a model hydrophobic drug. Microscopic and X-ray diffractogram (XRD) data indicated that the solubility of the drug in the films was ~1.5%. The inclusion of the hydrophilic polymer P3HPEI allowed rapid drug release within ~30 min, after which films disintegrated, demonstrating that the formulations are suitable for application to mucosal surfaces, such as in buccal drug delivery. Higher release with increasing drug loading allows flexible dosing. Blending P3HPEI with chitosan thus allows the selection of desirable physicochemical and mechanical properties of the films for delivery of haloperidol as a poorly water-soluble drug.